Pencegahan Tindak Kekerasan Seksual Pada Anak Melalui Sex Education - Hidayati, Dewi Ayu; Junaidi; Rochana, Erna; Pairsulsyah (Jurnal Pengabdian Dharma Wacana, 2025)
Early age sex education is very necessary as a form of prevention from sexual violence. Sex education can increase children's knowledge of the importance of protecting themselves, especially protecting the reproductive organs that are vulnerable to sexual violence. Based on this, there is a need for socialization and education to parents about the importance of sex education for children. The goal is to increase knowledge and understanding of sex education, as well as awareness of parents to instill the values ​​of sex education from an early age, so that it can prevent sexual violence against children. The methods that will be used in this community service activity are the preparation, implementation, evaluation and follow-up stages. The preparation stage is carried out in the form of planning and preparing the form of activities that will be carried out. The implementation stage is carried out in the form of socialization and education related to the importance of sex education for children. Evaluation stage, where the results of this activity are expected to increase understanding and knowledge about sex education that needs to be given to children. The results of this PKM activity show success because there has been an increase in participant knowledge by 8% and can be seen from the active participation and enthusiasm of participants during the material delivery session and discussions carried out in the activity. In conclusion, this community service can be a means of preventing sexual violence against children. The follow-up is needed for similar activities, so that it is beneficial for community life.